Single nucleotide polymorphisms in adiponectin and its receptors’ genes as potential risk factors for coronary artery disease in type 2 diabetes mellitus – an up-to-date overview - Szydełko, Joanna; Dąbrowska, Izabela (Journal of Education, Health and Sport, 2021)
Introduction: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disease with still growing incidence among adults and young people worldwide. Patients with T2DM are more susceptible to develop coronary artery disease (CAD) than non-diabetic individuals. Several pre-clinical and clinical studies suggested that adiponectin, a pleiotropic hormone with anti-atherogenic, anti-inflammatory, and insulin-sensitizing properties, may be a molecular link between metabolic and cardiovascular diseases. Aim of the study: This article summarizes the current knowledge on single nucleotide polymorphisms (SNPs) within the adiponectin and its receptors’ genes on the risk of CAD in patients with T2DM. Description of knowledge: Adiponectin, the most abundant circulating adipocytokine, is encoded by the Acrp30/adiponectin gene on chromosome 3q27, which constitutes a region specific for obesity-related metabolic syndrome. A genetic deficit of this adipokine may be responsible for the increased risk of CAD both in the general population and T2DM subjects. The results of recent years’ studies highlight that SNPs at the adiponectin locus, +45 T>G and +276 G>T as well within its two receptors, are determinants of early onset atherosclerosis in individuals with T2DM. Conclusions: SNPs in ADIPOQ, ADIPOR1 and ADIPOR2 may modify the risk of CAD in the group of patients with T2DM. SNP +45 and SNP +276 seem to be attractive, molecular markers for identification of diabetic individuals at especially high risk of CAD. The discovering of their exact mechanisms may result in novel screening options as well as diagnostic process and treatment scheme. Therefore, further research is required to determine the effects of adiponectin and its receptors’ polymorphisms and their roles in the pathogenesis of obesity-related metabolic diseases.